Imperial Sunset - Beloff, Max. author. aut Link
XIV, 412 p.
Keywords: An account of the British Empire, this study examines its transition into the Commonwealth, its policies towards defence, the effect of the world depression, the moves towards trusteeship and indirect rule, its part in World War II and the prospects for the future.